ANALISIS KEPUASAN KEPENTINGAN DALAM PENGADAAN BAHAN PUSTAKA DI PERPUSTAKAAN SEKOLAH - Ismurjanti, Ismurjanti; Putranda Setiawan, Ezra (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2019)
The growth of information technology becomes a challenge for the school librarian, especially in developing the book collections. Book procurement for the library must be matched with the library user’s need. In this research we develop a method to measure the library user’s opinion about the importance and performance of each kind of books in the library, in this case in a school library. The user’s opinions were obtained using questionnaire and analyzed by calculate the average of each score and placing each category in the importance-performance diagram. From the diagram, it could be observed which kinds of books should be added, weeded, or preserved in the library. Several adaptations could be carried out to implement this method outside the school library.